Differentiating the Associations of Waist Circumference and Body Mass Index With Cardiovascular Disease Risk in a Chinese Population. (March 2015) - Li, Rui; Shi, Liang; Jia, Jian; Li, Yanyun; Yang, Qundi; Ruan, Ye; Chen, Renjie; Kan, Haidong
It is not known which obesity index best explains variations in cardiovascular disease risk across populations. The objective of this study was to differentiate the associations of waist circumference (WC) and body mass index (BMI) with cardiovascular disease risk in a Chinese population. Cardiovascular risk factors, WC, and BMI were measured in 13 817 adults aged more than 18 years in Shanghai. Higher WC tertiles were associated with higher blood pressure and higher cholesterol, triacylglycerol, and glucose concentrations within each tertile of BMI and vice versa. The odds ratios (ORs) of hypertension, dyslipidemia, and metabolic syndrome increased with successive WC (or BMI) tertiles after adjustment for BMI (or WC) and several covariates. However, BMI tertiles were not associated with the ORs of diabetes after adjustment for WC. WC may be better than BMI as an alternative measure of body fatness or fat distribution for predicting diabetic risks in Chinese adults.